2002
DOI: 10.1046/j.1365-2672.2002.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Yarrowia lipolytica as a potential producer of citric acid from raw glycerol

Abstract: Aims: To study the biochemical response of Yarrowia lipolytica LGAM S(7)1 during growth on raw glycerol (the main by-product of bio-diesel production units) in order to produce metabolic products of industrial signi®cance. Methods and Results: Yarrowia lipolytica was cultivated on raw glycerol or glucose in¯asks. Although nitrogen-limited media were employed, growth was not followed by production of reserve lipid. Nitrogen limitation led to citric acid excretion. Growth and citric acid production parameters on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
254
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(287 citation statements)
references
References 30 publications
21
254
2
10
Order By: Relevance
“…A simple visual inspection and selection of morphologically distinct colonies were effective in capturing at least part of the microbial diversity of interest, demonstrating the potential to be a practical, relatively fast and less expensive technique for screening environmental samples for given purposes. Confirmation of the presence of bacteria and yeast among the isolates was relevant, since these are two important groups from the biotechnological viewpoint (e.g., Papanikolaou et al, 2002;Dharmadi et al, 2006). Interestingly, the presence of bands of slightly different sizes after amplification with the universal primers for yeast (Figure 2) suggests that possible variants of the species identified in databases, or even new species, may have been isolated in this work.…”
Section: Discussionmentioning
confidence: 58%
“…A simple visual inspection and selection of morphologically distinct colonies were effective in capturing at least part of the microbial diversity of interest, demonstrating the potential to be a practical, relatively fast and less expensive technique for screening environmental samples for given purposes. Confirmation of the presence of bacteria and yeast among the isolates was relevant, since these are two important groups from the biotechnological viewpoint (e.g., Papanikolaou et al, 2002;Dharmadi et al, 2006). Interestingly, the presence of bands of slightly different sizes after amplification with the universal primers for yeast (Figure 2) suggests that possible variants of the species identified in databases, or even new species, may have been isolated in this work.…”
Section: Discussionmentioning
confidence: 58%
“…The biomass concentration, substrate yields and specific growth rate of C. tropicalis and R. mucilaginosa cultured in flasks after 24 h are shown in ). Several researchers have demonstrate that cell growth and lipid content of different oleaginous yeast cells is lower in glycerol respect to other carbon source to the same concentration and showed their positive effect when it is used simultaneously with another energy source as xylose [29,30]. …”
Section: Influence Of Glycerol Concentrationmentioning
confidence: 99%
“…It has been reported that the yeast Yarrowia lipolytica produces the same amount of citric acid when grown on glucose or on crude glycerin (Papanikolaou et al, 2002). Several reports have also demonstrated that xanthan gum can be obtained from agricultural and industrial wastes using less expensive carbon sources to produce it, such as citric acid (Jana and Ghosh, 1995), cassava serum (Brandão et al, 2010) and milk whey Silva et al, 2009), since the utilization of glucose or sucrose is a critical factor in the production cost of this polysaccharide (Garcia-Ochoa et al, 2000).…”
Section: Xanthan Gum Production and Molecular Weightmentioning
confidence: 99%
“…A promising alternative use of this byproduct is the microbial conversion of crude glycerin through biotechnological processes (Johnson and Taconi, 2007;da Silva et al, 2009) into value-added products, like poly-3-hydroxybutyrate polymers (Zhu et al, 2010); clavulanic acid (Teodoro et al, 2010); recombinant human erythropoietin (Elik et al, 2008), and citric acid (Papanikolaou et al, 2002;Rywińska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%